O022/#296 The equity challenges of a large-scale ovarian cancer patient experience study in low- and middle-income countries: the every woman study™□ (2022). (4th December 2022) - Reid, Frances; Mackay, Clara; Lau, Iren; Noll, Florencia; Nasser, Sara; Refky, Basel; Mukhopadhyay, Asima; Adams, Tracey; Bolatbekova, Raikhan; Kaidarova, Dilyara; Funston, Garth; Phan, Ngoc; et al.
Abstract : Objectives: Ovarian cancer patient experience data is limited, especially in low- and middle-income countries (LMICs). The World Ovarian Cancer Coalition's online study in 2018 attracted 1531 responses from 44 mainly high-income countries. Recognising the need for robust data to support national efforts to improve women's survival and quality of life, the Coalition has partnered with the International Gynaecologic Cancer Society to adapt the Study for LMICs. Methods: An Oversight Committee featuring equal clinical/patient representation from major geographical areas identified 31 potential countries based on income status. The Committee oversees the Study's adaptation, advises on access issues, and applies a solutions-based approach to challenges. Results: 24 countries with up to 10 centres each are engaged, with a projected sample size of >2, 000 women. Countries and even centres vary widely in data collection and service organisation. For some, this is their first national or international collaboration. Challenges include: Ensuring participating centres reflect variety of care Accommodating variability of language, literacy, and internet connectivity (interview, paper, secure electronic link) Coverage of core expenses (translation, ethics submission) Ensuring patients and centres with least resource can participate Developing an equitable approach to publication opportunities Balancing countries' differing needs within the study approach Conclusions: A unified approach among and even within some LMICs is not feasible. A flexible and pragmatic approach with local teams as well as open channels of communication are essential to challenging inequities on this scale. This approach may add complexity to data analysis, but early benefits are being derived as LMIC patient voices are heard.